Endoscopic approaches to the paranasal sinuses and skull base : a step-by-step anatomic dissection guide - Bernal-Sprekelsen, Manuel; Alobid, Isam; Enseñat, Joaquim; Prats-Galino, Alberto (Thieme, 2017)
With the continuing evolution of endoscopic techniques for surgery of lesions of the paranasal sinuses and skull base, and the reduced morbidity associated with this minimally invasive modality, the method has gained widespread use in recent years. This work offers a thorough review of all endoscopic approaches for access to the nose and paranasal sinuses and, through them, to the skull base. Central to this guide is the emphasis on profound knowledge of the complex anatomy in this area, as well as the many vital structures that can be endangered there. To this end, more than 900 full-color im.